2021
DOI: 10.26434/chemrxiv-2021-6h2b7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substituent Control of σ-interference Effects in the Transmission of Saturated Molecules

Abstract: The single-molecule conductance of saturated molecules can potentially be fully suppressed by destructive quantum interference in their σ-system. However, only few molecules with σ-interference have been identified and the structure-property relationship remains to be elucidated. Here, we explore the role of substituents in modulating the electronic transmission of saturated molecules. In functionalized bicyclo[2.2.2]octanes, the transmission is suppressed by σ- interference when fluorine substituents are appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…The geometry optimization for each structure is performed to the forces smaller than 10 meV/Ang. The mean-field Hamiltonian obtained from the converged DFT calculation was combined with our home-made implementation of the non-equilibrium Green's function method, Gollum [19], to calculate the phase-coherent, elastic scattering properties of each system consisting of left gold LUMO gap, we found either the dotted lines of the monomer junctions are close to or below the solid lines of the trimer junctions. Therefore, the qualitative behavior over the range of energies is that the trimer-junction Seebeck coefficients are higher than those of the monomer junctions.…”
Section: Theoretical Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometry optimization for each structure is performed to the forces smaller than 10 meV/Ang. The mean-field Hamiltonian obtained from the converged DFT calculation was combined with our home-made implementation of the non-equilibrium Green's function method, Gollum [19], to calculate the phase-coherent, elastic scattering properties of each system consisting of left gold LUMO gap, we found either the dotted lines of the monomer junctions are close to or below the solid lines of the trimer junctions. Therefore, the qualitative behavior over the range of energies is that the trimer-junction Seebeck coefficients are higher than those of the monomer junctions.…”
Section: Theoretical Calculationmentioning
confidence: 99%
“…To increase the ZT of the molecular devices [14], various strategies have been investigated to improve RESEARCH ARTICLE the thermopower, including varying molecular length of organic building blocks [11,15,16], changing connectivity of molecular cores [17][18][19][20], tuning molecule-electrode coupling [21], exploring different anchor groups [22] and substituent groups [23], etc. More importantly, theoretical advances revealed that the intermolecular interactions, such as π-π stacking, will enhance ZT by suppressing the phonon contribution to lowering the thermal conductance [12], suggesting that the intermolecular interactions are essential for the design of molecular devices with high ZT [24,25].…”
Section: Introductionmentioning
confidence: 99%